Learning situations. Nature, significance and scope - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2023)
In their preamble, the royal decrees establishing the organization and minimum teaching, promulgated in the second quarter of the 2021/2022 academic year, state that "in order to facilitate teachers' own practice, a definition of a learning situation is proposed and guidelines for its design are set out". That is, it emerges "an effective tool for integrating curricular elements" with the aim of contextualizing, experiencing and transferring learning, as well as generating motivation and commitment to it.This article aims to analyze some pedagogical features and the study of certain normative provisions that give nature to learning situations. We will then try to assess whether the significance and scope of the regulation of the educational administrations estimate the main characteristics that the guidelines of the basic regulations outlined above enunciate, and guide teachers to plan their teaching activities in accordance with them.
Keywords: learning situations; context; experience; transfer; programming